Intraoperative Management of Adult Patients on Extracorporeal Membrane Oxygenation: An Expert Consensus Statement From the Society of Cardiovascular Anesthesiologists—Part I, Technical Aspects of Extracorporeal Membrane Oxygenation. (December 2021) - Mazzeffi, Michael A.; Rao, Vidya K.; Dodd-o, Jeffrey; Del Rio, Jose Mauricio; Hernandez, Antonio; Chung, Mabel; Bardia, Amit; Bauer, Rebecca M.; Meltzer, Joseph S.; Satyapriya, Sree; Rector, Raymond; Ramsay, James G.; et al.
Abstract : Extracorporeal membrane oxygenation (ECMO) is used to support patients with refractory cardiopulmonary failure. Given ECMO's increased use in adults and the fact that many ECMO patients are cared for by anesthesiologists, the Society of Cardiovascular Anesthesiologists ECMO working group created an expert consensus statement that is intended to help anesthesiologists manage adult ECMO patients who are cared for in the operating room. In the first part of this 2-part series, technical aspects of ECMO are discussed, and related expert consensus statements are provided.